1993
DOI: 10.3168/jds.s0022-0302(93)77406-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Quality and Evaporative Cooling on Lactational Performance of Holstein Cows in Hot Weather

Abstract: Twenty-four Holstein cows in midlactation during summer in southern Arizona were fed diets supplemented with a combination of blood, fish, and soybean meals (high quality protein) or corn gluten meal (low quality protein). Diets were balanced for CP content and estimated ruminal protein degradability, but they differed in Lys concentration (.98 vs. .59% of DM). Milk yield for the 56-d trial was higher by 11% for cows fed high than for cows fed low quality protein and higher by 9% for cows receiving evaporative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
1
10

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 13 publications
6
13
1
10
Order By: Relevance
“…However, Taylor et al (1991) reported that the cooled cows fed on low degradable protein produced more milk than the noncooled cows on high degradable protein or than either the cooled or the non-cooled cows on high degradable protein when thermal stress was high. Similar trend was also reported by Chen et al (1993). The relatively high protein content in the diets and enough rumen undegradable protein supply from all diets may have masked probable FM effect and protein sources × SF interaction on milk yield and DMI in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, Taylor et al (1991) reported that the cooled cows fed on low degradable protein produced more milk than the noncooled cows on high degradable protein or than either the cooled or the non-cooled cows on high degradable protein when thermal stress was high. Similar trend was also reported by Chen et al (1993). The relatively high protein content in the diets and enough rumen undegradable protein supply from all diets may have masked probable FM effect and protein sources × SF interaction on milk yield and DMI in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…The results reported in the literature with regard to the effect of FM on milk yield were inconsistent. Some studies (e.g., Chen et al, 1993) showed that FM improved milk yield due to supplying high amount of essential amino acids to the small intestine, but others (e.g., Santos et al, 1998) showed no positive effects. Furthermore, all diets used in the present studies were formulated with higher CP content than the requirements of the cows in mid lactation to alleviate the potential decrease in DMI during heat stress (Hassan and Roussel, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…An option to prevent this is to improve the quality of the protein being fed so that it may support increased milk levels in cows during heat stress (Huber et al, 1994). Researchers have found that supplementing with lysine led to increase in milk yields by 11% when fed to animals undergoing heat stress (Chen et al, 1993). During periods of heat stress, the effects of decreased DMI and increased maintenance requirements resulted in the animal metabolizing more protein in order to meet energy requirements compared with cows under moderate temperature environments (Beede and Collier, 1986).…”
Section: Strategies To Alleviate Heat Stress In Farm Animalsmentioning
confidence: 99%
“…Embora alimentos como o farelo de soja, casca de soja, farinha de carne e farinha de peixe tenham apresentado alta digestibilidade intestinal, alguns autores, citados por Cabral et al (2001), sugerem que a melhora no desempenho de vacas leiteiras de alta produção, adicionalmente à digestão intestinal, depende do perfil de aminoácidos dessas fontes, o qual deve complementar o perfil da proteína microbiana (CHEN et al, 1993;CLARK;KLUSMEYER;CAMERON, 1992;SCHWAB et al, 1992;BRODERICK, 1995). Figura 2.…”
Section: Resultsunclassified